HOW SHOULD SHARI’AH PRINCIPLES BE APPLIED IN MODERN COMPANY? - Susamto, Burhanuddin (Fakultas Syariah, 2012)
The purpose of this study is to show why the modern business institution (company) should be Islamized, and to suggest ways in which shari’ah principles can be applied in the company. To achieve this purpose, we should understand how company be islamized in comprehensive and integrated manner through the Islamic law perspective, with the contemporary issues like underlying contract of company, legal entity, and the concept of liability. The resolution of these issues is important to assert that shari’ah principles could be applied in the modern company by integrating approach. An integrating approach in the treating of these issues has, however, been lacking, nor has it been subjected to a thorough legal analysis through the principles of Islamic business law. Tujuan dari pembahasan ini adalah untuk menunjukkan bahwa institusi bisnis modern (perusahaan) harus diislamisasi, dan member masukan cara-cara bagimana prinsip- prinsip shari’ah dapat ditetapkan dalam perusahaan. Untuk mencapai tujuan ini, kita perlu memahami bagaimana perusahaan diislamisasi secara menyeluruh dan terintegrasi melalui perspektif hukum Islam terhadap persoalan kontemporer, seperti landasan kontrak perusahaan, badan hukum, dan konsep liabilitas. Solusi dari persoalan ini sangat penting untuk menegaskan bahwa prinsip-prinsip shari’ah dapat ditetapkan pada perusahaan modern melalui pendekatan integrasi. Bagaimanapun, pendekatan integrasi dalam menyikapi persoalan ini jarang dilakukan, disamping tidak menjadi tema analisis melalui prinsip-prinsip hukum bisnis Islami.